Karikatur und Zensur im preußischen Vormärz - Fischer, Hubertus (Studia Germanica Posnaniensia, 2018)
The author shows the interdependence in the development of caricature and cencorship in Prussia from the Congress of Vienna on to the Revolution of 1848. Within this framework he gives special notice to the short period of the so-called „freedom of picture“ 1842 to 43 and ist consequence for producing caricatures. The author's analysis of several caricatures points out general tendencies, and emphasizes the close interrelationship between caricature and literature. A summary with the main results and general statements on this subject concludes this essay.